Dynamics of service definitions—An explorative case study of the purchasing process of professional ICT-services. Issue 3 (September 2015) - Gelderman, Cees J.; Semeijn, Janjaap; de Bruijn, Anton
Abstract Recent studies on buying services have shown that service specifications and agreements present an on-going process in which service definitions evolve through buyer-service provider interactions. In the case of professional ICT services this interaction process is far from clear. Many organizations have been confronted with failing ICT projects, financial losses, and less-useable software and services. We investigated the procurement of professional ICT services in which stabilization and destabilization of specifications contributed to a successful sourcing process. We find that service definitions change during the purchasing process, induced by dissatisfaction about the current supplier, by new information from suppliers (market consultation), and by the need to clarify specifications for potential suppliers. Changing service definitions can be seen as 'business as usual' with collaborative suppliers. The results of this study indicate that relational governance plays a critical role in the purchasing process, supplemented by contractual governance. Contracts explicitly allow for adaptations of specifications within the agreed framework, stimulating and facilitating innovations and improvements by suppliers. This study challenges overoptimistic confidence in contracting, particularly performance-based, since specifications (including outcomes) cannot be agreed upon up-front in the case of professional ICT services.